Chapter 4 Family Supportive Supervisors Behaviour for the Sandwich Generation: Considerations for Training Practice - Miet Timmers; Tim Gielens (Emerald Publishing Limited, 2022)
This chapter explores the specific role employers and supervisors (SVs) can play in assisting the working sandwich generation (WSG) to find a good balance between work, dual care responsibilities and family. After a brief overview of the main concepts and ideas, the focus lies on the concept of family supportive supervisor behaviour (FSSB) defined as behaviours exhibited by SVs that are supportive of employees' family roles, in relation to health, well-being, and organisational outcomes. Based on the insights from qualitative research and a tested training concept, points of consideration are formulated for SVs in supporting the WSG. In addition to concrete tips in the area of general policy, learning objectives have been formulated for a supportive leadership style for the WSG, accompanied by a self-assessment tool.
10.1108/978-1-80262-501-120221005; 10.1108/978-1-80262-501-120221005; Working Women in the Sandwich Generation: Theories, Tools and Recommendations for Supporting Women's Working Lives; EBP077208358